The course of headache after the end of treatment with erenumab in patients with episodic and chronic migraine - Anna A. Garmanova; Anna V. Berdnikova; Nina V. Latysheva (LLC "MEDIAFORMAT", 2024)
Background. Migraine is the second most incapacitating disease and is accompanied by multiple comorbidities, especially in chronic migraines. Migraine treatment and improvement of the patients' quality of life are an important clinical issue. The calcitonin gene-related peptide (CGRP) monoclonal antibodies (mAbs) are the first target therapy for migraine. To date, there are no published data on the duration of effect after using mAbs. Aim. To determine the effect duration after cessation of erenumab treatment in patients with migraine. Methods. The study included 64 patients with migraine, who received at least three doses of erenumab; treatment was stopped when reduction of the headache frequency by at least 30% was achieved. The frequency of headache and migraine were assessed 1, 3 and 6 months after the end of treatment. Results. There was a significant increase in the frequency of headache compared to the values reported at the end of treatment, however, the rates were still significantly lower compared to the baseline values. In some patients, no increase in headache frequency following discontinuation of treatment was observed.